Molecular typing of Vibrio parahaemolyticus strains isolated from marine finfish/shellfish landed along south-west coast of India - Chakraborty, Rekha Devi; Surendran, P. K.; Joseph, Toms C (Indian Journal of Fisheries, 2013)
Vibrio parahaemolyticus is one of the most reported food-borne pathogen along the south-west coast of India, commonly occurring in marine fish. For epidemiological purposes, this pathogen is confirmed by various molecular typing methods, such as pulsed-field gel electrophoresis (PFGE) or ribotyping.These methods are labor intensive and time consuming. In the present study, rapid typing methods with specific sequences viz., conserved ribosomal gene spacer sequence (RS), repetitive extragenic palindromic sequence (REP), and enterobacterial repetitive intergenic consensus sequence (ERIC) and RAPD (random amplified polymorphic DNA) were used. Marine fish / shellfish were collected from major landing centers located along the south-west coast of India and screened for V. parahaemolyticus. Following phenotypic characterisation, fingerprinting of bacterial strains was carried out by various typing methods viz., RAPD, ERIC, REP, and RS PCR. Cluster analyses revealed the conglomeration of bacterial isolates into three and four groups using RAPD and RS respectively while it revealed two major groups in each of the ERIC and REP PCR methods. ERIC-PCR method generated two major clusters, one with the finfish and cephalopod isolates and the other with the strains isolated from shellfish samples suggesting that the strains isolated from finfish samples showed higher genetic similarity with the strains from cephalopods than that of shellfish isolates. However, RS PCR generated fewer amplified bands (eight) as compared to other typing methods, thus giving scope for higher discrimination of various V. parahaemolyticus strains, suggesting it as a reliable practical method for routine use.